Analisis pelaksanaan perjanjian sewa menyewa kios antara pihak BUMDes dengan penyewa : Studi Desa alas rajah - Sumriya Sumriya; Riesta Yoga Hastama; Linda uril khofifah (International Forum of Researchers and Lecturers, 2024)
the purpose of this study is to analyze the management of village property. Village property in the form of land and buildings that have been handed over for the economic progress of the village community which is invested in BUMDes on the basis of the season can be used optimally. So that it does not burden the village budget and expenditure. This study examines agreements by analyzing the application of legal principles of agreements in cooperation contracts for the management of village property leased to BUMDes and community management. The principles of treaty law which is a civil law concept applied in the concept of state administrative law become an interesting one because the agreement is in the regulation of private law and public law. Goverment contracts are routine goverment legal acts,to ensure legal certainty for the parties involved, legislation is needed that speciffcally regulates commercial contracts by the government both regarding procedures and limits of authorty.